Experimentally evaluation of high-performance concrete mixes used for tunnels and containing silica fume and polypropylene fiber after exposed to high temperatures (Fracture and Structural Integrity, 2022)
This work introduces an experimental study to evaluate the effect of elevated temperatures on the mechanical properties of high-performance concrete (HPC) mix with changes in Water-Cementitious ratios, W/(C+SF), Silica Fume percent, SF, and Polypropylene, PP, fiber contents. This mix was typically designed to satisfy the requirements of tunnel concrete. The compressive and indirect tensile strengths were measured at room temperature, RT, and after exposure to 400°C and 800°C. Moreover, SEM micrograph and EDS spot analysis tests were done to evaluate the effect of elevated temperatures. Fifteen mixes of HPC with different ratios of W/(C+SF), SF, and PP fiber were tested. According to the test results, the compressive strength values of design mixes increased significantly after exposure to 400°C. Moreover, using SF = 10%, the results indicated remarkable improvements in the compressive strength at 400°C and 800°C, in the case of the W/(C+SF) ratio of 0.31. On the other hand, the highest effect of the presence of PP fibers was 0.211, depending on variable ratios of the W/(C+SF) ratio and the SF content. In the case of PP=0.106 and SF=10%, the mass loss was higher at exposure to temperatures of 800°C.
Keywords: HPC; Compressive strength; Silica fume; Polypropylene fibers; Elevated temperatures; Mass loss